Analysis of the constrained action hypothesis and the effect of the focus of attention in balance on unstable platform - Candido, Cristiane Regina Coelho (2013)
The present study compared internal focus (IF) and external focus (EF) of attention and analyzed the constrained action hypothesis. For such, the balance performance in unstable platform was analyzed concurrently with reaction time task (probe). Twenty-two participants (16 and 17 years old) performed the balance task during 10s and responded to the auditory stimulus. In IF, participants were instructed to direct their attention toward the feet movements and to keep them in a horizontal position. In EF, participants were instructed to direct their attention toward the bottom of the platform seeking to prevent it touching the ground. No difference was found in the performance of the balance task and reaction time task between IF and EF (P>0.05). These results were explained by the experience levels of the participants in the task.